Ответ:
Объяснение:
4Al + 3O2 = 2Al2O3
Al(0) -3e = Al(+3) 4 ок-ие
в-ль
O2(0) +4e = 2O(-2) 3 в-ие
ок-ль
Al2O3 + 6HNO3 = 2Al(NO3)3 + 3H2O
Al2O3 + 6H(+) + 6NO3(-) = 2Al(3+) + 6NO3(-) + 3H2O
Al2O3 + 6H(+) = 2Al(3+) + 3H2O
Al(NO3)3 + 3NaOH = Al(OH)3 ↓+ 3NaNO3
2Al(OH)3 -> Al2O3 + 3H2O
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
4Al + 3O2 = 2Al2O3
Al(0) -3e = Al(+3) 4 ок-ие
в-ль
O2(0) +4e = 2O(-2) 3 в-ие
ок-ль
Al2O3 + 6HNO3 = 2Al(NO3)3 + 3H2O
Al2O3 + 6H(+) + 6NO3(-) = 2Al(3+) + 6NO3(-) + 3H2O
Al2O3 + 6H(+) = 2Al(3+) + 3H2O
Al(NO3)3 + 3NaOH = Al(OH)3 ↓+ 3NaNO3
2Al(OH)3 -> Al2O3 + 3H2O